The Draghi-Put: When unexpected words on joint liability speak louder than actions - Julia Wolfinger; Ekkehard Köhler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
This paper explores the process of re-convergence of GIIPS sovereign bond yields, which restarted in Q3 2012. We empirically analyse the impact of conventional and unconventional monetary policy and fiscal support measures in the EMU on bond pricing behaviour. We find that yield re-convergence of 2-, 5- and 10-year bond yield spreads and 5- and 10-year CDS spreads can be explained by crisis policy actions unknown to investors before uncertainty spread on markets.
Keywords: 330